Integrated crop management for vegetable production - M. Md. Jusoh (Malaysian Society of Plant Physiology, 2014)
IPM is now recognised as an important principle on which sustainable crop protection can be based. However, it is not holistic enough due to the tendency of current IPM program to excessively concentrate on a few insect pest problems only, rather than on a broader spectrum of crop pests and at the same time overlooking major agronomic, economic or social constraints`. The overall condition of the crop should become the major issue rather than the control of a single pest or disease. This approach has now evolved to what we termed as Integrated Crop Management (ICM). according to FAO (1991), `ICM embraces all activities in the production system and is composed of several management activities focusing on particular constraints, such as integrated pest management, integrated nutrientmanagement, integrated water management, and so on`. Therefore, ICM has been developed as a farming system to meet the requirements of long-term sustainability. It features a whole-farm strategy, which involves managing crop profitability, for the environment, in ways, which suit local soil, climatic and economic conditions. Based on this definition and features of ICM, our current vegetable crop protection endeavours in Malaysia are still not truly ICM. They are mainly IPM-based, for example that of brassicas and chillies. Looking at the requirements of ICM, the task of packaging ICM for every major vegetable grown in Malaysia is indeed daunting. However, for crop like cabbage and chili where IPM-based technoogy is already adequate, upgrading it to the ideals of ICM may be achievable within the next 3 or 4 years provided concerted research programs are initiated soon.